Integrated management of pests on onion and garlic - Soumia, P S; Karuppaiah, V; Singh, Major (Indian Horticulture, 2019)
Onion and garlic are most important vegetable and spice crops grownthroughout India. Like any other vegetables, full yield potential of both is notrealized due to a number of constraints. Among them, pests and diseases aremajor constraints in onion production. Onion thrips (Thrips tabaci), is the keypest of onion and garlic, causing 35-45% yield loss. Besides, it also acts asvector for various plant viral diseases. Pest and disease may occursimultaneously, while pest may even aggravate the disease severity.Although thrips remains the major pest, some other pests with less importancealso occurs sporadically. In recent times, impact of climate change is moreevident and visible with a shift of pest scenario, wherein the rise in temperaturemay facilitate mite infestation. To ward off these pests, farmers solely rely onchemical pesticides. However, chemo-intensive practice alone cannot provideadequate protection. This warrants an integrated approach to minimize theyield loss and to obtain good quality marketable bulb.